2009
DOI: 10.1039/b914417j
|View full text |Cite
|
Sign up to set email alerts
|

Neighbouring group participation vs. addition to oxacarbenium ions: studies on the synthesis of mycobacterial oligosaccharides

Abstract: Neighbouring group participation is frequently used to control the stereoselectivity of chemical reactions. Herein, we investigate the use of neighbouring group participation for the synthesis of disaccharides incorporating the mycobacterial sugar methylthioxylose. A bicyclic thioglycoside was activated by methylation to generate a methylsulfonium group that would act both as the anomeric leaving group, and also provide the methylsulfide group in the product. Model reactions indicated that the bicyclic interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 46 publications
2
42
0
Order By: Relevance
“…Although sulfonium ions of furanosides 58 have been used for the 1,2-cis selective glycosylation, the stereoselectivity of the thusobtained disaccharide 60 was moderate (α:β = 5:1) (Scheme 8). In this case, it was proposed that sulfonium ions work as a precursor of the glycosyl cation (oxonium ion), which is the real intermediate of glycosylation (24).…”
Section: E Glycosyl Sulfonium Ions Of Furanosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sulfonium ions of furanosides 58 have been used for the 1,2-cis selective glycosylation, the stereoselectivity of the thusobtained disaccharide 60 was moderate (α:β = 5:1) (Scheme 8). In this case, it was proposed that sulfonium ions work as a precursor of the glycosyl cation (oxonium ion), which is the real intermediate of glycosylation (24).…”
Section: E Glycosyl Sulfonium Ions Of Furanosidesmentioning
confidence: 99%
“…The "superdisarmed" donor is less reactive than the typical "disarmed" donor, which has 2,3,4,6-tetra-O-benzoyl protecting groups, because the 3,4,6-O-tribenzoyl work as electron-withdrawing groups and the 2-O-benzyl group does not work as a neighboring group (23). Turnbull and co-workers have already reported sulfonium ions of furanosides by the direct method using MeOTf (24).…”
Section: B Preparation Of Glycosyl Sulfonium Ionsmentioning
confidence: 99%
“…On the other hand, neighbouring hydroxyl groups of the donor could show influence on the anomeric preference through their protecting substituents, many of which were routinely exploited in various glycosylation methods, such as 2-O-ester-type [8][9][10] or 2-O-picolyl-type [11][12][13] for 1,2-trans glycosylation, and several sulfide auxiliaries [14][15][16][17][18] as well as intramolecular aglycon delivery IAD-type 19,20 for 1,2-cis glycosylation reactions.…”
mentioning
confidence: 99%
“…The use of the NPPOC photolabile protecting group in the synthesis of glycopyranosides has been explored (Yi et al, 2009) and the synthesis of pseudooligosacchasrides using cross-metathesis methods (Ronchi et al, 2009) and pseudodisaccharides based on neamine have also been described (Pang et al, 2009). Several studies on the control of glycosylation reactions have also been reported (Belen Cid et al, 2009;Xiaoning Li et al, 2009;Stalford et al, 2009). Studies towards the synthesis of C-glycosyl amino acids have been described using C-glycosyl 2-iodopropanes and the chiral auxiliary camphorsultam glyoxylic oxime ester (Bragnier et al, 2009).…”
Section: Carbohydratesmentioning
confidence: 99%